Situation Report: Romania, 28 February 1978 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. After the Andrei Visit to Budapest Annual Plan Fulfillment Report for 1977 New Ways to Implement the 1978 Investment Plan Imbalances in Industrial Development Criticized Promises of "Artistic Freedom" Not Kept